An industrial quality control study on Melawares Manufacturing Corporation - De Guzman, Philip Revo P.; Pangilinan, Olive S.; Tuliao, Princess Dyanne B.
This is an industrial quality control study of Melawares Manufacturing Corporation, the leading melamine product manufacturer in the Philippines. The company is currently experiencing high rejection rates and is in need of a quality control study to detect the possible causes of those rejects. The company is also considering the implementation of a viable sampling plan in place of 100% inspection since some of its customers are currently inspecting based on a specific sampling plan. The study aims to analyze the company's production process and its current product status. The study is limited to plates since plate production comprises majority of the company's production. The team also limited the scope to plain plates since the design component of the plate involves another field of study. The group gathered the company's plate production data for the months of July and August and established pareto charts for each colored plain plate since data are attributes and are classified as either defective or non-defective only. The group also established Pareto charts, Ishikawa diagram, Quality Function Deployment (QFD), and Failure Modes, Effects and Criticality Analysis (FMECA) for problem analysis. The analysis shows that operators' inefficiency and material defects and age are the primary causes that affect high rejection rates. This conclusion is based on a table of the condition of outliers and from there assignable causes are determined. Revised control charts were made and only 1/3 of the original samples are noted as stable. Process capability analysis also resulted in a conclusion of unstable & defective and incapable process. It is thus concluded that the process has high variability and is very unstable. Recommendations were made as to the process improvement and consistency through standardization and operator training, material monitoring and the use of more standard quality control tools. A proposed sampling plan was also established and should be implemented if process stability is already achieved. Cost benefit analysis of these recommendations were also made to strengthen their viability.